PEMBELAJARAN MENULIS PUISI DENGAN MENGGUNAKAN METODE OUTDOOR STUDY PADA SISWA KELAS X SMAN 1 KATAPANG - Riski Ismawarni Merryanty; Senny Nuraeni; Via Nugraha (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The subject of this study is the results of evaluating poetry writing for students who do not reach the indicators of learning success in the curriculum so that the researcher offers a solution that is a recognized learning method that is more effective in improving students' ability to write poetry using the Outdoor study method. The formulation of the problem formulated in this study is about how the results of poetry writing skills using the outdoor study method? This study aims to determine the results of poetry writing skills using the outdoor study method. The method used in this study is the experimental method. The instrument for collecting data in this study uses the initial test sheet and the final test. Based on the results of the research, the students' ability to write poetry texts obtained an average initial test score of 43,0 and after using the outdoor method the study of poetry writing learning obtained an average value of 64,5. So, it can be concluded that the application of the outdoor study method to learning poetry text writing in class X SMAN 1 Katapang is able to improve student learning outcomes.